A interseccionalidade de gênero e classe na atenção à saúde: discurso de profissionais e mulheres em situação de rua - Araújo, Débora Cherchiglia de Moraes (Universidade Federal de São Carlos, 2024)
Introduction: Homelessness represents a serious global public health problem. When analyzing gender issues, studies show that women living on the streets are faced with several challenges, including low health care coverage and the scarcity of policies with an emphasis on health care. Objective: To analyze the meanings produced by homeless women and professionals regarding health care for this population. Methods: Qualitative study; theoretical framework: Intersectionality; methodology: French-based Discourse Analysis. It was developed at the Centro Pop and Casa de Acolhimento in the municipality of Arararaquara, São Paulo, from October to December 2022. 15 subjects participated, 08 women living on the streets for at least six months; and 07 professionals working in the care network for homeless women in the municipality, with at least 6 months of experience in the position answered the questions in a semi-structured script that were audio-recorded, transcribed in full and analyzed with the help of the Atlas.Ti software version 23.2.1. Results: Three discursive blocks emerged, “Being on the streets is not a fatality, but a process”, “Unveiling the markers: Gender and Poverty in health aspects”, “Duality between frustration and empathy: the daily life of professionals in caring for homeless women”. In the first block, the discourses produced by homeless women are presented, highlighting that living on the streets refers to darkness, an environment full of suffering; in addition to being considered a place of deprivation of food, sleep and rest, hygiene and water, which causes greater susceptibility to diseases. Furthermore, the interdiscourse of violence and gender permeates the ideological construction of these women, being more susceptible to Sexually Transmitted Infections and other pathologies with greater emphasis on mental disorders. In the second block, the meanings produced by homeless women about the intersection of gender and class from a health perspective are presented, highlight the need for a more comprehensive look at these women in full of their needs, given the low coverage of preventive exams for cervical and breast cancer; the association of care only being given during the pregnancy-puerperal cycle, in addition to the interdiscourse of drug use interpellated by mental illnesses. In the third block, the meanings produced by professionals are presented, showing that the work aimed at homeless women is challenging but at the same time interesting. Despite the actions aimed at women's health being of an immediate nature, professionals are concerned about the health of these women, and emphasize the need for improvements in the coordination between health and social assistance services, in addition to highlighting that the The implementation of Street Clinic Teams is necessary. Conclusion: In view of the above, we highlight the need of expanding the perspective of federal, state and municipal managers towards homeless women, as, despite being fewer in number, they have different health needs that need to be seen in full.
The intersectionality of gender and class in health care: discourse of professionals and homeless women
Keywords: Pessoas em situação de rua; Homelees persons; Saúde da mulher; Women’s health; Interseccionalidade; Intersectionality; Análise de discurso; Discourse analysis; Atenção à saúde; Health care; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE